2017
DOI: 10.28945/3685
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Readiness to Implement Digital Curriculum in Kuwaiti Schools

Abstract: Aim/Purpose: The goal of this study was to investigate how Kuwaiti teachers perceive their own readiness to implement digital curriculum in public schools, and the factors that affect Kuwaiti teachers’ readiness to implement digital curriculum from their perspectives. Background: In order to shift from the traditional instructional materials to digital and more innovative resources, teachers have to be prepared for the transformational curriculum. Teachers need to acquire all the technical and pedagogical sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The results are divergent (e.g. see Norizan et al, 2018;Tondeur et al, 2017 on a low level; Ng & Cheng, 2019;Noh et al, 2013;Al-Awidi, 2017 Furthermore, it should be noted that while this inquiry mainly focused on the construct of readiness on blended learning transition, the qualitative results inevitably and constantly probed different facilitating and hindering factors. The vast body of researches highlights a complicated pattern of interconnected factors related to readiness and is expected to be predictors of the successful integration of technology in education (Player-Koro, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are divergent (e.g. see Norizan et al, 2018;Tondeur et al, 2017 on a low level; Ng & Cheng, 2019;Noh et al, 2013;Al-Awidi, 2017 Furthermore, it should be noted that while this inquiry mainly focused on the construct of readiness on blended learning transition, the qualitative results inevitably and constantly probed different facilitating and hindering factors. The vast body of researches highlights a complicated pattern of interconnected factors related to readiness and is expected to be predictors of the successful integration of technology in education (Player-Koro, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that determining the readiness of teachers is necessary for the success of the different modalities of technology integration (Balajadia, 2015;DiBella et al, 2015;Markle, 2016;Al-Awidi & Aldhafeeri, 2017;Barde, 2017;Maimun et al, 2017;Christensen & Knezek, 2017;Cuhadar, 2018;Norizan et al, 2018;Ifinedo et al, 2019;Mousa & Kalonde, 2019;Ng & Cheng, 2019;Zamir & Thomas, 2019;Brooks & Grajek, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These make them ready to get involved in identifying children with dyslexia. Several studies in other teaching contexts such as using technology in teaching have shown similar results where teacher knowledge is positively correlated with their readiness to play the expected role (e.g., Al-Awidi & Aldhafeeri, 2017;Sulaiman, Hamzah, & Rahim, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…Technology has great potential to improve the quality and academic results of the teaching process. Therefore, it is necessary to identify various kinds of problems and facts in the field related to teachers' ability, some of which may not be ready and some are ready to integrate technology [45]. The results showed that ICT application in learning had been supported by the availability of supporting facilities and infrastructure.…”
Section: B Discussionmentioning
confidence: 99%
“…Besides, students' ability as learning subjects in operating computers was included in the good category. The success of ICT-assisted learning or electronic-based learning, in fact, must be supported by infrastructure, materials, utilization systems, and policies that have been established as regulations, both by the government and schools [45,46]. Empirically, teachers have implemented technology-assisted learning, such as the use of presentation media and instructional videos, but in some cases, it is still necessary to develop the learning potentials or resources available in schools.…”
Section: B Discussionmentioning
confidence: 99%